Variable filtered photographic film as a radiation detector for environmental radiation monitoring - Abdul Majid, Zafri Azran; Junet, Laila Kalidah; Hazali, Norazlanshah; Abdullah, Abdul Adam; Megat Hanafiah, Megat Ahmad Kamal (American Institute of Physics, 2013)
Environmental radiation is an ionising radiation that present in the natural environment which mostly originates from cosmic rays and radionuclide agents in the environment. This may lead the population to be exposed to the radiation. Therefore, the environmental radiation needs to be observed cautiously to minimize the impact of radiation. However, there is no specific or proper monitoring device that provides an outdoor environmental radiation monitoring. Hence, a new outdoor environmental radiation monitoring device was developed. A photographic film has been chosen as a dosimeter. The purpose of this study was to prove the covered photographic film attached with variable filter can be used to develop environmental radiation monitoring device to detect the ionising radiation. The filter used was variable thickness of plastic, aluminium (Al) and lead (Pb). The result from the study showed that the mean optical density (OD) values for medium speed film are in the range 0.41 to 0.73, and for fast speed film the OD values are in the range 0.51 to 1.35. The OD values decreased when the filter was attached. This has proven that the photographic film can be used to detect radiation and fast speed film was more sensitive compared to medium speed film.